Decoding HuH-7: a comprehensive genetic and molecular portrait of a widely used hepatocellular carcinoma model - Luis, Dario Dourado; Liehr, Thomas; Kankel, Stefanie; Weise, Anja; Pentzold, Constanze; Buhl, Eva M.; Hardt, Katharina S.; Keller, Diandra T.; Schröder-Lange, Sarah K.; Weiskirchen, Ralf (Frontiers in Cell and Developmental Biology, 2025)
IntroductionImmortalized cell lines play a crucial role in biomedical research by enabling reproducible experiments and enhancing our understanding of complex diseases. HuH-7, originally derived from a human hepatocellular carcinoma, is particularly valuable for studying liver cancer dynamics, viral hepatitis, and drug metabolism. However, concerns about cell line misidentification and genetic drift in cell lines highlight the importance of rigorous authentication to maintain the reliability of research outcomes, despite their widespread use.MethodsIn this study, we present a detailed (cyto)genetic and molecular analysis of HuH-7 cells, focusing on their hepatocellular characteristics and potential applications in translational research. Through thorough genomic profiling and next-generation mRNA expression analyses, we aimed to confirm the authenticity of the cell line and identify key genetic signatures associated with tumorigenic pathways. Results and DiscussionOur results emphasize the importance of regular identity verification, such as short tandem repeat (STR) profiling, and demonstrate how subtle genetic variations can affect phenotypic traits relevant to modeling liver disease. By providing insights into the genetic and transcriptomic features of HuH-7 cells, this study establishes a robust basis for future research and therapeutic investigations using this widely accepted liver cell model. It also emphasizes the importance for maintaining high-quality standards and robust authentication practices to ensure that cell-based studies produce reliable and reproducible results.